ChatGPT-Powered Meaning Reconstruction in the Chinese Translation of Dewey’s Experience and Nature - Zhang, Jinpei (International Journal of Linguistics and Translation Studies, 2025)
Experience and Nature is widely regarded as one of John Dewey’s most profound yet challenging philosophical works, often leaving both readers and translators perplexed. The advent of ChatGPT offers a promising tool to assist translators in navigating the muddy terrain of Dewey’s metaphysical discourse. This study explores how ChatGPT when deliberately prompted within the analytical framework of Systemic Functional Linguistics (SFL), can support the interpretation and reconstruction of experiential, interpersonal, and textual meanings in the translation process. Drawing on illustrative examples, the paper demonstrates ChatGPT’s potential to clarify philosophical jargon, unpack grammatical metaphors, analyze transitivity patterns, and propose coherent thematic structures. These findings offer practical insights for future translators and suggest that with the aid of ChatGPT and other large language models (LLMs), a revised and more accurate Chinese translation of Experience and Nature is within reach.